2007
DOI: 10.1136/ard.2007.071936
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes from studies of antineutrophil cytoplasm antibody associated vasculitis: a systematic review by the European League Against Rheumatism systemic vasculitis task force

Abstract: Objectives: We undertook a systematic literature review as a background to the European League Against Rheumatism (EULAR) recommendations for conducting clinical trials in anti-neutrophil cytoplasm antibody associated vasculitis (AAV), and to assess the quality of evidence for outcome measures in AAV. Methods: Using a systematic Medline search, we categorised the identified studies according to diagnoses. Factors affecting remission, relapse, renal function and overall survival were identified. Results: A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
258
8
41

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 373 publications
(323 citation statements)
references
References 59 publications
(91 reference statements)
16
258
8
41
Order By: Relevance
“…In MPA, immune deposits on the vessel wall are usually absent, and serum antineutrophil cytoplasmic antibodies (ANCAs) are frequently present. MPA shares these characteristic features with other ANCA-associated vasculitides (AAVs) such as granulomatosis with polyangiitis (Wegener's) (GPA), eosinophilic GPA (Churg-Strauss), and renal limited vasculitis (1,2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In MPA, immune deposits on the vessel wall are usually absent, and serum antineutrophil cytoplasmic antibodies (ANCAs) are frequently present. MPA shares these characteristic features with other ANCA-associated vasculitides (AAVs) such as granulomatosis with polyangiitis (Wegener's) (GPA), eosinophilic GPA (Churg-Strauss), and renal limited vasculitis (1,2).…”
mentioning
confidence: 99%
“…In patients with MPA, a wide range of organ systems can be affected (1)(2)(3). The lung is one of the major organs involved, and recent studies demonstrated that pulmonary involvement is associated with unfavorable outcomes (4,5).…”
mentioning
confidence: 99%
“…Long-term maintenance therapy may be achieved with a variety of immunomodulatory drugs, including methotrexate and azathioprine [150]. The survival rate for patients with WG is estimated to be 74 to 91% at 5 years [136,151].…”
Section: Wegener's Granulomatosismentioning
confidence: 99%
“…In a recent study in which all patients were treated with high-dose corticosteroids to induce remission, rituximab was shown to be as good as cyclophosphamide for treating AAVs and better than cyclophosphamide for patients with relapsingremitting disease [147,148]. The survival rate for MPA is reported to be 45 to 76% at 5 years [136,151].…”
Section: Microscopic Polyangiitismentioning
confidence: 99%
See 1 more Smart Citation